Keterampilan Komunikasi Interpersonal Dalam Menjaga Hubungan Yang Sehat Dan Produktif Di Era Digital Dalam Lingkup Mahasiswa Pariwisata Universitas Brawijaya - Jean Aril Farisma; Nurul Pringgowati; Arsih Amalia Chandra Permata (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This research focuses on how interpersonal communication in the digital age is affected by advances in information technology, especially the internet and social media. The research identifies negative impacts on the depth of interpersonal relationships and verbal communication skills through an emphasis on digital distraction, over-reliance on written media, and lack of emotional engagement. However, there are opportunities to enhance creativity in intercultural communication and collaboration along with these challenges. Overcoming the lack of emotional engagement requires improving verbal and listening skills as well as wise control of digital distractions. In short, to be relevant and significant in the dynamics of the digital age, interpersonal communication methods must be adjusted.